Atomic and electronic structures of Si/Ge(100) interfaces studied by high-resolution photoelectron spectroscopy and scanning tunneling microscopy - Kuzmin Mikhail; Lehtiö Juha-Pekka; Jahanshah Rad Zahra; Sorokina SV; Punkkinen Marko PJ; Laukkanen Pekka; Kokko Kalevi (AMER PHYSICAL SOC, 2022)
The close similarity of silicon and germanium, isoelectronic group-IV elements, makes the integration of Ge layers on Si substrates suitable for technology development, but the atomic and electronic structures of Si1-xGex surfaces are still an open issue, in particular, for the alloy systems where Si is deposited on the Ge substrate. In this study, utilizing low-energy electron diffraction, scanning tunneling microscopy, and photoelectron spectroscopy using synchrotron radiation, we demonstrate that the formation mechanisms of the Si-on-Ge structures are controlled by two interface phenomena, namely Si indiffusion and Ge segregation on top of this surface. Employing these phenomena and controlling the Si quantity, one can synthesize the well-defined crystalline Ge-(2 x 1)/Si1-xGex/Ge(100) stacks where the number of Si atoms at the host Ge lattice sites can be tuned. Using the obtained data on the atomic and electronic structures of such systems, we also propose a method for interface engineering of Ge/Si/Ge stacks with tailored properties as promising templates for growing the device junctions.